STRATEGI HIDUP PETANI PADI SAWAH DI DESA TUMANI SELATAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Glandie ., Runturambi; Elsje Pauline Manginsela; Olly Esry Harryani Laoh (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the life strategy of wetland rice farmers in Tumani Selatan Village, Sub-District of Maesaan, South Minahsa Regency. This research was conducted for three months from September to November 2018. The data used in this study were primary and secondary data. Primary data collection through direct interviews with 15 respondents of paddy rice farmers based on a questionnaire that had been prepared previously. Secondary data was collected from the office of Desa Tumani Selatan, from the internet through google searching regarding the profile of South Minahasa Regency, and from previous research documents that were relevant to this study. Data analysis in this study is quantitative and qualitative analysis which is presented in the form of a table, then described descriptively. The results of the research that have been done show that the life strategy of the upper class of farmers applies two strategies, namely the accumulation strategy and consolidation strategy. Middle class farmers apply accumulation strategies. While the lower class farmers implement a survival strategy.*eprm*